2021
DOI: 10.3390/mi12020142
|View full text |Cite
|
Sign up to set email alerts
|

Potential Whole-Cell Biosensors for Detection of Metal Using MerR Family Proteins from Enterobacter sp. YSU and Stenotrophomonas maltophilia OR02

Abstract: Cell-based biosensors harness a cell’s ability to respond to the environment by repurposing its sensing mechanisms. MerR family proteins are activator/repressor switches that regulate the expression of bacterial metal resistance genes and have been used in metal biosensors. Upon metal binding, a conformational change switches gene expression from off to on. The genomes of the multimetal resistant bacterial strains, Stenotrophomonas maltophilia Oak Ridge strain 02 (S. maltophilia 02) and Enterobacter sp. YSU, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Not only zinc but also lead and cadmium greatly increased the expression of zntA , in a process uncontrolled and mediated through zntR ( Binet and Poole, 2000 ). zntR and zntA genes were located at different locations on the chromosome ( Baya et al, 2021 ). This confirms our findings about the lead resistance of E. kobei FACU6.…”
Section: Discussionmentioning
confidence: 99%
“…Not only zinc but also lead and cadmium greatly increased the expression of zntA , in a process uncontrolled and mediated through zntR ( Binet and Poole, 2000 ). zntR and zntA genes were located at different locations on the chromosome ( Baya et al, 2021 ). This confirms our findings about the lead resistance of E. kobei FACU6.…”
Section: Discussionmentioning
confidence: 99%
“…zntA is significantly induced by lead and cadmium not by zinc only, its expression is uprgulated and is mediated by zntR (Binet and Poole 2000 ). z ntR and zntA genes are not adjacent to each other but are located on different locations of the chromosome (Baya et al 2021 ). So, this supports our results of R. planticola FACU 3’s ability to resist lead.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the presence of quinone reductase gene ( chrR ) helps in reducing of chromate thus in chromate bioremediation (Eswaramoorthy et al 2012 ; Paul et al 2020 ). There are gene systems/gene cluster encoded for copper hemostasis like cop operon, cutC, cue O and cue R in addition to cus operon and pco/sil operon which participates in silver efflux system (Franke et al 2003 ; Gudipaty et al 2012 ) and found on the chromosome as several studies reported that these genes are regularly be located on the chromosome of Enterobacteriaceae species not restricted to plasmid (Baya et al 2021 ). The presence of mer R which is a transcriptional regulator for mercury resistance may be evidence of R. planticola FACU 3 may be mercury resistant bacteria (Brown et al 2003 ).…”
Section: Discussionmentioning
confidence: 99%